Facades Integrated Solar-thermal Collectors – Challenges and Solutions. (March 2017) - Visa, Ion; Moldovan, Macedon; Comsit, Mihai; Neagoe, Mircea; Duta, Anca
Abstract: The Solar Heating and Cooling Roadmap (2014) set a main focus "on increasing the share of solar thermal energy for the domestic hot water and space heating demand per building, from about 25% to about 60%" with installed systems on or near the buildings. The suitable implementation area at building level is limited, and optimally oriented facades have to be considered. Facades integration adds pre-requisites to the design specifications of the solar thermal collectors, mainly related to the architectural acceptance and good conversion efficiency. A novel solar-thermal collector was developed to specifically address the main challenges brought by facades implementation. The collector with trapeze shape (0.67m 2 active area, 69.42% nominal efficiency) is used as building block in arrays with various surface areas, shapes and colors, well matching the variety of the buildings facades. A comparative analysis of the solar-thermal arrays of three trapeze collectors and traditional rectangular collectors is presented in the paper. Three facades of single- and three of multi-family houses are comparatively analyzed considering architectural acceptance, functionality, durability (limited tracking) and thermal power output.